KOMPETENSI PENGAWASAN ANGGOTA DPRD DALAM PENGGUNAAN APBD DISPENDA KOTA PONTIANAK - E.21107027, Nahdin (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
This paper is motivated by the human resource competencies legislators in APBD monitoring Pontianak is low, and therefore this paper focuses on the competence of DPRD Member Supervision Department in the Use of APBD revenue Pontianak is studied based on knowledge, skills and self-concept. Knowledge legislators to basic competencies needed in monitoring the use of APBD is still not adequate. Because most of the members of the council still has not mastered the basic principles of accounting, performance budgeting, budgeting techniques and principles of accountability. Expertise in performing supervisory councilors APBD usage, still needs to be improved, including through; Bimtek-Bimtek and assistance as well as sending the members to attend seminars and workshops both locally and nationally, as well as carry out a comparative study. In general, councilors had an attitude which uphold and respect differences of opinion that occur in the field. As a solution put forward the following suggestions: competency enhancement program should be tailored to the specific needs of the local legislators mainly Pontianak City Commission C, so the technical guidance and workshops that have relevance to the duties given council members are concerned, should the implementation of comparative studies, and workshops Bimtek followed seriously by council members, because of the attitude and behavior of councilors who are not serious in following programs to improve the competence and councilors are expected to make value as a reference in supervising the use of APBD.Â Keywords: supervisory competence members of Parliament, the use of APBD.